Quasi-polymeric construction of stable perovskite-type LaFeO3/g-C3N4 heterostructured photocatalyst for improved Z-scheme photocatalytic activity via solid p-n heterojunction interfacial effect - Wu, Yan (2020)
Materials of perovskite-type structure have attracted considerable attention for their applications in photocatalysis. In this study, a novel composite of p-type LaFeO3 microsphere coated with n-type nanosized graphitic carbon nitride nanosheets was constructed by the quasi-polymeric calcination method with the aid of electrostatic self-assembly interaction. Results indicate that the LaFeO3/g-C3N4p-n heterostructured photocatalyst obtained, in contrast to the pure constituents, enabled improved visible-light absorption, and more efficient separation and migration of charge carriers via solid p-n heterojunction interfacial effect. Correspondingly, the LaFeO3/g-C3N4 composite allowed for higher visible-light-responsive photocatalytic activity for the degradation of Brilliant Blue, which was 16.9 and 7.8 times that of pristine g-C3N4 and LaFeO3, respectively. The photocatalytic degradation of Brilliant Blue was ascribed to the combined contributions of the photogenerated holes (h+), superoxide radicals (O2-) and hydroxyl radicals (OH). Based on solid p-n heterojunction interfacial interaction, a Z-scheme charge carrier transfer pathway integrated with the dye-sensitization effect is proposed as the underlying mechanism of the photocatalytic reaction process. Therefore, we believe that the perovskite-type LaFeO3/g-C3N4 Z-scheme photcatalyst promotes the development of photocatalysis and holds much promise for environmental remediation.